Experiences and needs of older adults at different stages of cerebral infarction based on trajectory theory-A qualitative study - Xianping Tang; Hong Sun; Song Ge; Shuyu Han; Ying Li; Bei Wu (Wiley, 2023)
Abstract Background In recent years, stroke has become the second leading cause of death worldwide, and the incidence and mortality of ischemic stroke have increased significantly. This study mainly aimed to explore the experiences and needs of older adults at different stages of cerebral infarction based on the chronic illness trajectory theory. Methods Data were collected from 22 older adults experiencing the onset, acute, and stable stages of stroke through semi‐structured interviews and were analyzed using Colaizzi's descriptive phenomenological approach. Results Multiple themes and subthemes emerged on the experiences and needs of older adults at different stages of cerebral infarction based on the three dimensions of the long‐term disease trajectory theory: illness‐related work, biographical work, and everyday life work. Seven themes were extracted for illness‐related work, six for biographical work, and eight for everyday life work. Discussions The treatment, nursing, and rehabilitation of cerebral infarction are complex. This study indicated that patients after cerebral infarction have different experiences and needs for illness‐related work. They also have distinctive and dynamically changing demands for biographical work and everyday life work. Conclusions The experiences and needs of older patients with cerebral infarction changed dynamically at different stages of the disease. Healthcare professionals should develop effective interventions targeting these needs at various disease stages, provide patients with continuous support to shape their disease trajectories, and maintain patients' stability.